Conversion of Cellulose to 5-HMF in the Presence of Silica-Alumina Catalysts Synthesized by Dual Template at Low Temperature - Hosgun, Halit; Topçu, Özlem; Hosgun, Emir Zafer; Bozan, Berrin (My University, 2023)
In this study, which incorporates many principles of green chemistry (use of renewable feedstocks, catalysis, improvement of energy efficiency, and harmless solvents and auxiliaries), the single-phase catalytic conversion of cellulose to 5-HMF in over silica-alumina catalysts was investigated. A series of dual-template silica-alumina catalysts with CTAB as the main template and F127 or triethylamine (TEA) as the co-template were synthesized at a low temperature of 60 °C and characterized by XRD, N2 adsorption-desorption technique, FT-IR and pyridine adsorption FT-IR. The surface area is increased by using the second template in silica-alumina catalyst. In addition, the acidity of the surface was changed by using the second template. The cellulose conversion and yield of 5-HMF increased from 36% to 52% and from 3.13% to 4.24%, respectively, due to the properties gained by using the second template. 52% cellulose conversion and 8.13% selectivity of 5-HMF were obtained in aqueous medium, 220 °C and 6 h reaction time with the catalyst using TEA as co-template. Eco-friendly silica catalysts synthesized at low temperatures with a dual template can be considered as a potential alternative for the conversion of cellulose into value-added biobased products.
Keywords: Green chemistry; Cellulose; heterogeneous catalysis; 5-HMF